2016
DOI: 10.1007/s11103-016-0460-0
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of NaCl-treated Limonium bicolor leaves reveals the genes controlling salt secretion of salt gland

Abstract: Limonium bicolor, a typical recretohalophyte that lives in saline environments, excretes excessive salt to the environment through epidermal salt glands to avoid salt stress. The aim of this study was to screen for L. bicolor genes involved in salt secretion by high-throughput RNA sequencing. We established the experimental procedure of salt secretion using detached mature leaves, in which the optimal salt concentration was determined as 200 mM NaCl. The detached salt secretion system combined with Illumina de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 72 publications
2
104
0
Order By: Relevance
“…Transcriptomic analysis of developing Limonium bicolor leaves while monitoring salt gland developmental stages suggests that salt gland development might be regulated by transcription factors homologous to those regulating trichome development in Arabidopsis thaliana , however, this suggestion is based solely on correlated expression patterns and weakly documented evidence for orthology (Yuan et al, 2015b, 2016b). Yuan et al (2014) have further developed a transformation system for L. bicolor to enable validation of predicted gene functions within the native genome.…”
Section: New Genetic Resources and Tools Provide Insights Into The Momentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptomic analysis of developing Limonium bicolor leaves while monitoring salt gland developmental stages suggests that salt gland development might be regulated by transcription factors homologous to those regulating trichome development in Arabidopsis thaliana , however, this suggestion is based solely on correlated expression patterns and weakly documented evidence for orthology (Yuan et al, 2015b, 2016b). Yuan et al (2014) have further developed a transformation system for L. bicolor to enable validation of predicted gene functions within the native genome.…”
Section: New Genetic Resources and Tools Provide Insights Into The Momentioning
confidence: 99%
“…Faraday and Thomson (1986a) reported ion efflux rates in Limonium perezii salt glands that were significantly higher than rates possible exclusively via transmembrane transport. Congruently, Yuan et al (2016b) have reported genes associated with vesicle function enriched in Limonium bicolor leaves upon NaCl treatment. Vesicle-mediated NaCl transport may provide the energy efficiency required for transporting salts through the salt glands that may not be feasible via transmembrane ion channels alone.…”
Section: New Genetic Resources and Tools Provide Insights Into The Momentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive oxygen species (ROS), such as superoxide anion radicals, hydroxyl radicals, and hydrogen peroxide, are natural by‐products of aerobic metabolism . In cells, mitochondria are the primary source of endogenous intracellular reactive species.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…These stresses can affect nutrient uptake and utilization; therefore, plants have developed a wide variety of structural, morphological, and regulatory adaptations to address these environmental stresses . In particular, multi‐level regulatory mechanisms involved in salt tolerance have been well characterized in halophytes, such as Suaeda salsa, Thellungiella salsuginea , and Limonium bicolor . Adaptations to cold stress, drought, and UV radiation have also been reported to a lesser degree.…”
Section: Introductionmentioning
confidence: 99%